Effect of Dew and Raindrops on Electric Field around EHV Transmission Lines - Budi Utama; Asniar Aliyu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper analyses the change of electric field in the proximity of 500 kV extra high voltage (EHV) transmission lines, in the presence of raindrops and dew. The computations were carried out using MatLab software by solving the electrostatic equations. The analysis depicts that the spatial distribution of the electric field strength varies with water drop content along the lateral distance along the transmission line. The peak electric field reduces with the water drop content, whereas the electric field remains the same at around 36 m from the transmission line. Then onwards the field strength increases with the water drop content. At long distances the field strength is not affected by the water drops. Such variation is highly important to analyse the adverse effects on the insulators used in HV applications. The results are of high significance to a country such as Indonesia where the precipitation levels are generally high in most parts of the country.